2022
DOI: 10.1029/2022jb024113
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Control on Seismic Rupture and Earthquake Sequence Along the Yingxiu‐Beichuan Fault With Implications for the 2008 Wenchuan Earthquake

Abstract: The May 12, 2008 M w 7.9 Wenchuan earthquake, which caused over 69,000 fatalities, is one of the most devastating earthquakes in China. Located along the boundary between the Tibetan Plateau and Sichuan Basin, the Wenchuan mainshock ruptured a total of ∼290 km along the Longmenshan (LMS) fault zone, involving three fault segments: Yingxiu-Beichuan Fault (YBF), Xiaoyudong fault, and Pengguan fault (Figure 1a) (Liu-Zeng et al., 2009;X. Xu et al., 2009). Most of the coseismic slip occurred along the YBF, which ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 101 publications
(228 reference statements)
0
1
0
Order By: Relevance
“…(2022) found that fault geometry controlled the rupture propagation of the 2020 Jiashi earthquake. Furthermore, the earthquake cycle simulations also recognized the impact of geometric factors on rupture behaviors (Yu et al., 2018; Zhang et al., 2022b). Therefore, in addition to stress and frictional heterogeneities, fault geometry may also play a important role in the complexity of rupture behavior.…”
Section: Introductionmentioning
confidence: 99%
“…(2022) found that fault geometry controlled the rupture propagation of the 2020 Jiashi earthquake. Furthermore, the earthquake cycle simulations also recognized the impact of geometric factors on rupture behaviors (Yu et al., 2018; Zhang et al., 2022b). Therefore, in addition to stress and frictional heterogeneities, fault geometry may also play a important role in the complexity of rupture behavior.…”
Section: Introductionmentioning
confidence: 99%